2017
DOI: 10.1063/1.4984964
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Theory and simulation of hybrid halide perovskites

Abstract: Organic-inorganic halide perovskites present a number of challenges for first-principles atomistic materials modeling. Such “plastic crystals” feature dynamic processes across multiple length and time scales. These include the following: (i) transport of slow ions and fast electrons; (ii) highly anharmonic lattice dynamics with short phonon lifetimes; (iii) local symmetry breaking of the average crystallographic space group; (iv) strong relativistic (spin-orbit coupling) effects on the electronic band structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
105
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 132 publications
(198 reference statements)
10
105
0
1
Order By: Relevance
“…This is calculated by subtracting the energy of the shifted minimum on the conduction band from the minimum of the same band at the high symmetry R‐point, in which, the shifted band minimum is located at k 0 = 0.052 Å −1 . This result is consistent with most of the previous studies that have shown that the band splitting occurs at the conduction band edge for Pb‐based compounds . However, as shown in Figure A), the valence band edge also splits into two spin‐polarized bands.…”
Section: Computational Details Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is calculated by subtracting the energy of the shifted minimum on the conduction band from the minimum of the same band at the high symmetry R‐point, in which, the shifted band minimum is located at k 0 = 0.052 Å −1 . This result is consistent with most of the previous studies that have shown that the band splitting occurs at the conduction band edge for Pb‐based compounds . However, as shown in Figure A), the valence band edge also splits into two spin‐polarized bands.…”
Section: Computational Details Results and Discussionsupporting
confidence: 93%
“…Yet the SOC is found to have a profound effect on the magnitude of the bandgap for this polymorph, thus reducing substantially its value by 1.01 eV. A similar feature is notable of the data listed in Table for MAPbI 3 , in agreement with literature …”
Section: Computational Details Results and Discussionsupporting
confidence: 89%
“…The calculated band gap values are in excellent agreement with the experimental value (i. e., 1.6 eV). Nevertheless, although non‐relativistic DFT calculations were shown to be accurate for the structural properties, it was also previously recognized that the agreement for the band gap is the result of a cancellation of errors occurring from the neglect of spin‐orbit couplings (decreasing the band gap) and from the missing correlation effects in the DFT approximation (increasing the band gap). Additionally, Figure shows that the six lowest geometries are comprised in an energy range of about 0.003 Ry (i. e., 0.041 eV) corresponding to about 1.5 kT (i. e., 0.039 eV) at room temperature, whereas the other structures are found with energies of more than 0.008 Ry (i. e., 0.11 eV) above the global minimum.…”
Section: Resultsmentioning
confidence: 99%
“…[15] In parallel to the development of solar cells and to the increase of their efficiencies, a significant number of experimental and theoretical works have concentrated on understanding the fundamental properties of perovskite materials. In the case of MAPbI 3 , these investigations have for example focused on the structural and electronic properties, [16][17][18][19][20][21] (band gap, band structure, dielectric constant, etc), the effects of the orientational disorder of the MA cations in the crystal structure, [18,[22][23][24][25][26][27][28] the effects of temperature, [29][30][31] the absorption spectrum, [32][33][34][35][36] or the strong vibrational signal in IR and Raman spectra. [37,38] MAPbI 3 is known to adopt three different phases depending on the temperature, [39,40,24] namely the orthorhombic phase is inherent below~165 K, the tetragonal phase between~165 K and~327 K, and the cubic phase above~327 K. In particular, the positional disorder of the MA cations increases with the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Because shallow states are energy states formed near the VB or CB mobility edges, generally they are considered to be benign and offer a useful means to modulate semiconductor electronic properties. For example, although shallow defect states can also trap charge carriers, because of the relatively low activation energy required for these trapped charges to be excited to mobility edges, detrapping events occur at a relatively high rate, that is, most of these trapped charge carriers can be thermally released to the bands before recombination can occur inducing minimal influences on charge‐carrier transport . On the other hand, intrinsic defects of low‐coordinate Si atoms at the surface or dangling bonds introduce deep levels within the Si band gap that lead to decrease in the overall carrier transport efficiency.…”
Section: Introductionmentioning
confidence: 99%